Penggunaan Ganja Medis dalam Pengobatan dan Pengaturannya di Indonesia - Putranto, Mahardian; Arie Mangesti, Yovita (Journal Evidence Of Law, 2024)
Medical marijuana (Cannabis sativa) has been used since ancient times. Its use is written in medical books from China, India and even the Mesopotamian era. In these records, the use of marijuana (Cannabis sativa) is not only as a medicine, but also as a food ingredient and a ritual tool. A popular issue in Indonesia today is about legalization of medical marijuana. Marijuana is a class I narcotic which is written in the law. Cannabis has a very high potential to cause addiction and not be used for therapy. However, several institutions have discussed that marijuana can be legalized in Indonesia. Cannabis can provide health benefits and has economic potential. Marijuana contains cannabinoids that are considered to have medical benefits. Several countries have developed marijuana into legal medicinal preparations. Economically, medical marijuana has great potential as an export commodity. The approach in this study uses a qualitative method by using data from books, regulations, expert opinions, as well as examining various scientific journals using Garuda, PubMed, Sciencedirect, and Wiley. The result of data analysis is in the form of systematic information. This article can be a reference for development and legalization of medical marijuana in Indonesia.